Comparison of the cleaning effectiveness of pulsed vacuum cleaning and disinfection machine versus spraying cleaning and disinfection machine for rigid endoscope instruments - Li, Jian; Hu, Yue; Bo, Licong; Wang, Xue; Hu, Wenjing (The Journal of Infection in Developing Countries, 2026)
Background: This study aims to compare the cleaning effectiveness of the pulsed vacuum cleaning and disinfection machine (PVD) and the spraying cleaning and disinfection machine (SCD) in cleaning rigid endoscope instruments. Methodology: A total of 900 postoperative rigid endoscope instruments from the sterilization supply room of our hospital, collected between July and December 2024, were included in the study. Instruments were randomly divided into two groups using a computer-generated random number sequence, ensuring a 1:1 allocation ratio: the research group (450 items) and the control group (450 items). The research group used the PVD machine, while the control group used the SCD machine. The sterilization effectiveness, cleaning quality, ATP bioluminescence assay, and protein residue measurement were compared between the two groups. Results: The sterilization time in the research group was longer than that in the control group. The instrument damage rate and endotoxin positive rate were significantly lower in the research group (p < 0.05). The research group showed significantly higher results in the paper test method compared to the control group (p < 0.05). No significant difference was found between the two groups in visual inspection and blood residue comparison (p > 0.05). The ATP bioluminescence detection and protein residue pass rates were higher in the research group than in the control group, with a statistically significant difference (p < 0.05). Conclusions: The pulsed vacuum cleaning and disinfection machine performs better than the spraying cleaning and disinfection machine in cleaning rigid endoscope instruments, offering potential benefits for patient safety and instrument longevity.